Radiographic Predictors of Reoperation in Adolescents Undergoing Hip Preservation Surgery for Femoroacetabular Impingement. Issue 3 (March 2023) - Serbin, Philip A.; Youngman, Tyler R.; Johnson, Benjamin L.; Wilson, Philip L.; Sucato, Dan; Podeszwa, David; Ellis, Henry B.
Background: Femoroacetabular impingement (FAI) is a condition caused by repetitive abutment of a morphologically abnormal proximal femur and/or acetabulum that may result in chondral and labral pathology. An understanding of radiographic parameters associated with successful primary surgery has not been well established. Purpose: To determine preoperative radiographic parameters that predict reoperation for FAI and correlate radiographic measurements with outcomes in these patients. Study Design: Case-control study; Level of evidence, 3. Methods: A prospectively collected institutional registry of adolescent patients (age, <19 years) who underwent surgery for FAI (arthroscopic/open) was reviewed. Preoperative standing anteroposterior pelvic radiographs were analyzed for femoroepiphyseal acetabular roof (FEAR) index, as well as lateral center-edge angle (LCEA) and alpha, Tönnis, and Sharp angles. Patient-reported outcomes (PROs) (modified Harris Hip Score, Hip disability and Osteoarthritis Outcome Score) were analyzed preoperatively and at 1- and 2-year followup. Radiographic indication of risk for reoperation was evaluated using receiver operating characteristic (ROC) analysis. Spearman correlation was calculated between radiographic measurements and PROs at 2 years postoperatively. Results: A total of 81 patients (91 hips) underwent primary surgery (57 surgical dislocations vs 34 arthroscopies) for FAI. The mean age at time of primary operation was 16.23 years (range, 10.4-19.6 years) (73.6% female). Eleven hips (12.1%) underwent reoperation at a mean of 20.6 months from primary surgery. The LCEA, FEAR index, Tönnis angle, and Sharp angle before index surgery were significantly different ( P < .05) between patients who underwent reoperation and those who did not. ROC analysis indicated that LCEA <22°, FEAR index >–8.7°, Tönnis angle >6.0°, and Sharp angle >44° were predictors for increased risk of reoperation. Using the cutoff values from the ROC analysis in this series, 43% of patients with an LCEA ≤22° had a repeat procedure, while only 8% of those with an LCEA >22° had a repeat procedure. Similar trends were seen with the other aforementioned acetabular radiographic measurements (FEAR index, Tönnis angle, Sharp angle). Patients who did not require a reoperation demonstrated significant improvement in all PRO categories from their preoperative to 2-year postoperative visits ( P < .0001). Conclusion: In patients undergoing treatment for FAI, a reoperation was associated with radiographic signs of hip dysplasia, indicating that patients with a shallower acetabulum are at risk for a repeat operation.